Beyond the sea… The Neolithic transition in the southwest of France. (20th March 2018) - Perrin, Thomas; Manen, Claire; Valdeyron, Nicolas; Guilaine, Jean
Abstract: The neolithisation of the South of France occurred in several stages and involved different processes. During the first half of the sixth millennium cal. BC, the first Neolithic installations were sporadic settlements of pioneering groups from Italy. During the second stage, several centuries later, many Neolithic sites appeared, first of all, along the Mediterranean shore, and then later further inland. The settlement of the hinterlands, particularly in the Southwest of France, led to a relatively marked recomposition of the technical and economic framework of Neolithic societies, which has at times been attributed to interactions with groups of hunters. However, the critical examination of the available data, supported by new radiocarbon dates, shows that very few sites used up until now to discuss this scenario can actually be considered to be reliable. Two new ongoing excavations illustrate the complexity of the sedimentary and taphonomic processes of multi-phased archaeological infillings and provide more reliable new data. This dual approach, combining the reassessment of former data with new primary evidence, brings to light the overly binary emphasis on the traditional division between Mesolithic hunters and Neolithic farmers; as the human groups involved in the neolithisation process can represent a number of intermediary situations.